2015
DOI: 10.1121/1.4921288
|View full text |Cite
|
Sign up to set email alerts
|

The underwater sound field from vibratory pile driving

Abstract: Underwater noise from vibratory pile driving was observed using a vertical line array placed at range 16 m from the pile source (water depth 7.5 m), and using single hydrophones at range 417 m on one transect, and range 207 and 436 m on another transect running approximately parallel to a sloping shoreline. The dominant spectral features of the underwater noise are related to the frequency of the vibratory pile driving hammer (typically 15-35 Hz), producing spectral lines at intervals of this frequency. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
3
17
0
4
Order By: Relevance
“…On the contrary, the secondary noise path, which consists of the Scholte waves, seems to govern the noise field in the seawater at low frequencies in the vicinity of the seabed surface. This is again in line with the measurements presented in [29], albeit for a different installation setup and pile dimensions, in which it was observed that the Scholte mode contributes to more than 30 dB in the 63-Hz octave band. • The pressures in the water column are significantly lower when compared to the ones generated by the impact hammer.…”
Section: Noise Prediction During Installation With a Vibratory Devicesupporting
confidence: 91%
See 4 more Smart Citations
“…On the contrary, the secondary noise path, which consists of the Scholte waves, seems to govern the noise field in the seawater at low frequencies in the vicinity of the seabed surface. This is again in line with the measurements presented in [29], albeit for a different installation setup and pile dimensions, in which it was observed that the Scholte mode contributes to more than 30 dB in the 63-Hz octave band. • The pressures in the water column are significantly lower when compared to the ones generated by the impact hammer.…”
Section: Noise Prediction During Installation With a Vibratory Devicesupporting
confidence: 91%
“…This is in line with the observations and the model developed by Dahl et al [29] in which the vibratory pile source is modeled as an incoherent line source (and not as a coherent one with a predefined time delay, as was the case when impact piling was examined). As mentioned in [29], any sense of line-source spatial coherency is lost or at the very least rendered vastly more complex with effects not observable in the ensuing pressure field. In other words, the Mach wave radiation from a coherent source traveling down the pile surface is not seen in the case of vibratory piling.…”
Section: Noise Prediction During Installation With a Vibratory Devicesupporting
confidence: 87%
See 3 more Smart Citations